THE EVOLUTION OF THE WINTER PARALYMPIC GAMES AND SPORTS - Vasilios, Giovanis; Eriketti, Margari (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: The aim of this research was to record and the evolution of the winter paralympic games and sports since 1976 until 2010. The history of the Winter Paralympic Games is relatively recent compared to that one of the Olympic Games. The first Games were held in 1976 in Ornskoldsvik, Sweden and the most recent, 38 years later in 2014, in Sochi, Russia. This article will examine the Winter Paralympic Games up until the ones in 2010 in Vancouver, Canada. During these years, there have been many changes in relation to the Games itself, the governing body of the Paralympic Movement, the sports’ facilities, the sports involved and sports’ categories. The motivation for writing this paper was the need to record and gather all of these items in one paper. Gathering information for the Winter Paralympic Games will be an important theoretical background. This information will create a database for the structure of the governing body of the Paralympic Games, for the organization of the Games [Local Organizing Committee (LOC), venues and equipment], for the evolution of the Winter Paralympic Sports and the categories of the athletes, as well as the evolution of the athletes’ and sports’ participation. Material : The research material that was used was mainly from the bibliography and records of the International Paralympic Committee (IPC), from the Official Post Games Reports and the Internet, while the research method that was used was descriptive. Moreover, the use of diagrams will depict the distribution of the participation of athletes and countries in each Games. Results : The participation of countries grew continuously and steadily from 16 to 44, during the years of 1976 to 2010 respectively. Regarding the athletes’ participation, starting in the first Games with 198 athletes, they reached the number of 502 in the 2010 Vancouver Winter Paralympic Games. The participation percentages of the athletes coming from Europe constituted the bulk of the total participation from the Continents throughout the journey of the Games (1st Winter Paralympic Games: 95% - 10th Winter Paralympic Games: 61%). The proportion of men was at all events greater than that of the women. Starting with only two categories of impairment being part of the first Games (athletes with amputation and athletes visually impaired), in the 2010 Winter Paralympic Games in Vancouver, almost all categories were included (except the athletes with an intellectual disability). Conclusions : The sports included in the 1st Paralympic Games were the events of Alpine Skiing and one event of Cross Country Skiing, while in the 10th Paralympic Games were included all the disciplines of Alpine skiing and Cross-Country Skiing, Ice Sledge Hockey and Wheelchair Curling.